Breeding of Promising New Short- Climbing Forms of Squash - Rakhmanovna, Aripova Shakhnoza; Dusmuratova, Saodat Ismailovna (International Journal on Integrated Education, 2023)
For the selection work in 2012 the samples of squash 0044SQ (Holland) and BT+KB-001 (Turkey) were selected from the gene pool of the Research Institute of Plant Industry of Uzbekistan. In 2013, the above squash specimens were studied in a nursery of source material, in which they were evaluated on biological and economically valuable features. As a result, they were identified as short-climbing, transportable, high-yielding squash lines LZ-2513 and LH-1916. The promising squash line LZ-2513 or the new variety Orbit was selected by selection from squash sample 0044SQ (Holland), and the line LH-1916 or the new variety Viridi by selection from sample BT+KB-001 (Turkey). Breeding work was carried out in 2014-2018. In 2019-2020 competitive varietal trials were conducted in comparison with the variety standard Unumdor, included in the State Register of the Republic of Uzbekistan. In the process of breeding there were selected zucchini lines LH-1916, or new variety Viridi with elongated fruits of dark green color from sample BT+KB-001 (Turkey) and LZ-2513, or new variety Orbit with rounded fruits of light green color from sample 0044SQ (Holland).